2005
DOI: 10.1089/dis.2005.8.93
|View full text |Cite
|
Sign up to set email alerts
|

Physician Attitudes Regarding Cardiovascular Risk Reduction: The Gaps Between Clinical Importance, Knowledge, and Effectiveness

Abstract: Reducing risk factors for patients with vascular disease can reduce the subsequent incidence of cerebro-cardiovascular disease. While physicians have had extensive training in the importance of atherosclerotic vascular disease risk factor modification, evidence suggests that they systematically miss opportunities for clinical prevention during routine practice. The aim of this study was to identify whether physicians felt confident in their knowledge and effectiveness regarding counseling patients to reduce ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
2
19
1
2
Order By: Relevance
“…Other studies have shown that although a majority of individuals with lifestyle-related diseases are willing to alter their diet to a more healthy one, a considerable proportion are not living according to this will to do so [20]. Healthcare professionals refer to low patient compliance [21] and lack of patient interest [22,23] as barriers to disease prevention. Yet another reason behind professionals' rather negative judgements concerning their patients' willingness to change might be unrealistic and even idealistic expectations in respect of lifestyle change.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that although a majority of individuals with lifestyle-related diseases are willing to alter their diet to a more healthy one, a considerable proportion are not living according to this will to do so [20]. Healthcare professionals refer to low patient compliance [21] and lack of patient interest [22,23] as barriers to disease prevention. Yet another reason behind professionals' rather negative judgements concerning their patients' willingness to change might be unrealistic and even idealistic expectations in respect of lifestyle change.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses and doctors are often not motivated to deliver cessation interventions as they perceive it to be outside their roles. A survey of US physicians found that whilst the majority (62%) were confident about their knowledge of the benefits of smoking cessation, few (14%) offered it in practice [102]. High patient volume and complexity of the health issues in presenting patients are also reported as factors that limit the time available for effective smoking cessation counseling [103].…”
Section: Just Focus On Treating the Conditionmentioning
confidence: 99%
“…2,6,11 Cardiovascular risk reduction (CRR) programs address modifiable risk factors and have demonstrated appreciable reductions in morbidity and mortality from CVD. 4,6,[11][12][13][14][15] Unfortunately, Canadian physicians have limited time to counsel their patients regarding CRR. 16 The focus of doctor-patient interactions tends to prioritize diagnosis and management of established medical disease.…”
Section: Résumémentioning
confidence: 99%